2013
DOI: 10.1128/jcm.02652-12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Benchtop HIV Ultradeep Pyrosequencing Drug Resistance Assay in the Clinical Laboratory

Abstract: f Detection of low-abundance drug resistance mutations (DRMs) of HIV-1 is an evolving approach in clinical practice. Ultradeep pyrosequencing has shown to be effective in detecting such mutations. The lack of a standardized commercially based assay limits the wide use of this method in clinical settings. 454 Life Sciences (Roche) is developing an HIV ultradeep pyrosequencing assay for their benchtop sequencer. We assessed the prototype plate in the clinical laboratory. Plasma samples genotyped by the standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 27 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…Using deep sequencing, a series of studies have demonstrated the ability to detect minority HIV drug resistant variants at levels as low as 0.1% to 1% of the virus population [26, 106, 158162]. Most of these studies used the 454™ platform [106, 158, 159, 163, 164], but recently other deep sequencing technologies such as Illumina® [165] and Ion Torrent™ [162, 166] have proved to be useful in the identification of low-level drug resistant HIV variants. Deep sequencing has been used in HIV drug resistance surveillance [167, 168], to study transmission of HIV drug resistant viruses [101, 160, 169175], and to evaluate the impact of minority variants on treatment efficacy [160, 176183].…”
Section: Deep Sequencing In the Clinical Settingmentioning
confidence: 99%
“…Using deep sequencing, a series of studies have demonstrated the ability to detect minority HIV drug resistant variants at levels as low as 0.1% to 1% of the virus population [26, 106, 158162]. Most of these studies used the 454™ platform [106, 158, 159, 163, 164], but recently other deep sequencing technologies such as Illumina® [165] and Ion Torrent™ [162, 166] have proved to be useful in the identification of low-level drug resistant HIV variants. Deep sequencing has been used in HIV drug resistance surveillance [167, 168], to study transmission of HIV drug resistant viruses [101, 160, 169175], and to evaluate the impact of minority variants on treatment efficacy [160, 176183].…”
Section: Deep Sequencing In the Clinical Settingmentioning
confidence: 99%
“…The laboratory manipulations necessary for library generation are recognised as potential sources of artefactual recombination. Several papers have addressed the issue of minimising PCR artefacts [ 1 - 3 ] and there is growing interest in optimising RT-PCR techniques to enable accurate analysis of patient RNA virus load and early detection of the emergence of drug resistant quasi-species [ 3 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, and although this is still uncertain, drug-resistant HIV-1 minority variants (i.e., those present in as low as 1% of the viral population) have been suggested to be clinically relevant, as they have a high chance of selection under antiretroviral drug pressure conditions (49)(50)(51)(52)(53)(54)(55)(56)(57). For that reason, a series of ultrasensitive assays have been developed to detect drug-resistant HIV-1 minority variants, e.g., allele-specific PCR (49,58), oligonucleotide ligation assays (33,59), and deep (next-generation) sequencing (60)(61)(62). On the other hand, as described above, the adoption of genotypic HIV-1 tropism assays in the clinical setting has been hampered by the limited sensitivities of the population-based sequencing assays to detect minor non-R5 variants.…”
mentioning
confidence: 99%